2022
DOI: 10.1155/2022/1912603
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Image Encryption Technique Based on Cyclic Codes over Galois Field

Abstract: In the modern world, the security of the digital image is vital due to the frequent communication of digital products over the open network. Accelerated advancement of digital data exchange, the importance of information security in the transmission of data, and its storage has emerged. Multiple uses of the images in the security agencies and the industries and the security of the confidential image data from unauthorized access are emergent and vital. In this paper, Bose Chaudhary Hocquenghem (BCH) codes over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Be that as it may, the primary downside of the GoogleNet was its heterogeneous geography that should be modified from module to module. Another constraint of GoogleNet was a portrayal bottleneck that definitely decreases the element feature in the next layer and hence at times may prompt loss of helpful data [41][42][43][44][45][46][47].…”
Section: Related Workmentioning
confidence: 99%
“…Be that as it may, the primary downside of the GoogleNet was its heterogeneous geography that should be modified from module to module. Another constraint of GoogleNet was a portrayal bottleneck that definitely decreases the element feature in the next layer and hence at times may prompt loss of helpful data [41][42][43][44][45][46][47].…”
Section: Related Workmentioning
confidence: 99%
“…These estimations recommend that CNNs might have exceptionally huge execution contrasts when distinguishing the presence of spatial examples. The case wherein the sign can show up in one of a few areas and found that CNN spatial affectability compares to IO [27][28][29][30][31][32][33]. Nonetheless, CNN affectability was far underneath ideal in distinguishing some complicated surface examples.…”
Section: A Challengesmentioning
confidence: 99%
“…In addition, its accuracy of results is much higher than other various algorithms. [42], [64][65][66][67][68][69][70].…”
Section: Estimation Model/regression Techniques a Random Forestmentioning
confidence: 99%